Safety, Clinical Outcome, and Fracture Rate of Femoropopliteal Stenting Using a 4F Compatible Delivery System. Issue 2 (February 2015) - Sarkadi, H.; Bérczi, V.; Kollár, A.; Kiss, D.; Jakabfi, P.; Végh, E.M.; Nemes, B.; Merkely, B.; Hüttl, K.; Dósa, E.
Abstract : Objective: To determine the safety, clinical outcome, and fracture rate of femoropopliteal interventions using 4F stents. Methods: Between January 2010 and December 2011, 112 symptomatic patients were treated by stent implantation. Ten patients were lost to follow up; therefore, 102 patients (62 men; mean age 66.4 ± 10.1 years) were retrospectively analyzed. The indication for femoropopliteal revascularization was severe claudication (Rutherford–Becker score = 3) in 63 (62%) patients and chronic critical limb ischemia (Rutherford–Becker score = 4–6) in 39 (38%). Follow up included palpation of peripheral pulses and measurement of ankle brachial index. In patients with suspected in-stent restenosis duplex ultrasonography was performed. In 2013, patients were asked to return for a fluoroscopic examination of the stents. Results: 114 lesions (Trans-Atlantic InterSociety Consensus-C and D, n = 45) were treated with 119 stents (Astron Pulsar, n = 42; Pulsar-18, n = 77). Lesions were long (≥100 mm) in 49 cases and heavily calcified in 35. Stents were long (≥120 mm) in 46 cases. Ten stents were partially overlapped. The technical and clinical success rates were 100%. Two puncture related complications were noted, neither of which required surgical repair. Eleven patients died (myocardial infarction, n = 4; stroke, n = 2; cancer, n = 5) and nine patients underwent major amputation (above knee, n = 4). The primary patency rate was 83% at 6 months and 80% at 12 months. The primary assisted patency rate was 97% at 6 months and 94% at 12 months. The secondary patency rate was 86% at 6 months and 85% at 12 months. The prevalence of fractures was 26% (type III and IV, 10%) after an average follow up of 25 months. Conclusion: Femoropopliteal stenting using a 4F compatible delivery system can be accomplished with a low complication rate, acceptable fracture rate, and with similar 12 month patency and revascularization rates as their 6F counterparts.